the Review and Critique of the Book “The Tragedy of Great Power Politics” - Hasan Pourahmadi; Amir Abbasi Khoshkar (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
In the foregoing research, the critique and evaluation of John J. Mearsheimer's book "The Tragedy of Great Power Politics" is done in two levels: form criticism and content criticism. At the level of form criticism, the book is in good standing in terms of printing, page layout, and typographical errors, and at the content level, the book is written in a positivist way with the acceptance of realistic assumptions. Ignoring the economic and cultural components that underlie international relations and disregard for other non-state actors' involvement in international interactions are among the content shortcomings of the book. In content criticism with the Islamic approach, the ethical, value, and belief conflicts of the Islamic view in international relations with the book can be one of the criticisms of the approach to offensive realism. Supporting domestic researchers and developing theorization scientific space in two dimensions of scientific and financial support for research projects are among the suggested strategies to reach the desired point in native and Islamic theorizing.